Influenced but Unaware: Social Influence on Alcohol Drinking Among Social Acquaintances. (3rd March 2014) - Dallas, Rebecca; Field, Matt; Jones, Andrew; Christiansen, Paul; Rose, Abi; Robinson, Eric
<x xml:space="preserve">Abstract</x> Background Drinking partners may be influenced by each other's alcohol consumption. However, these effects have only been shown in artificially created social pairings and typically among same‐sex young adults. Here, we test whether similarly strong influence effects occur among "real" pairs of social acquaintances (friends and partners) and whether people are aware of this influence on their alcohol consumption. Methods Forty‐six pairs of social acquaintances aged between 19 and 60 years old participated in a between‐subjects experiment, in a semi‐naturalistic bar laboratory setting. One member of each pair (the confederate) was randomly selected and asked to consume only alcoholic (alcohol condition) or soft drinks (nonalcohol condition), while the pair completed a game together in a bar setting. The other participant (naïve) was unaware of these drinking instructions. Postconsumption, we measured the extent to which naïve participants believed that their partner had influenced their own drinking behavior. Results A large effect of condition on alcohol consumption was observed, χ² (2) = 15.8, p < 0.001, Cramer's V = 0.59, whereby the number of alcoholic drinks selected by naïve participants in the alcohol confederate condition was significantly greater than in the nonalcohol confederate condition. The majority of naïve participants (81%) also tended to be unaware that their partner had influenced their alcohol consumption. Conclusions Social acquaintances are influenced by each other's alcohol consumption and may not be aware of this influence on their behavior.